2021
DOI: 10.7759/cureus.20542
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Toward Using the Triple Combination Bleaching Formula and Related Outcomes: A Cross-Sectional Study

Abstract: IntroductionKligman's formula is a topical triple combination consisting of hydroquinone, tretinoin, and topical corticosteroid. It has recently become widely popular among the general population for different purposes. Its improper use can lead to unsatisfactory results and unpleasant side effects. AimThis study aimed to assess the attitude, satisfaction, and complications related to topical usage of Kligman's formula among the general population in Saudi Arabia. Materials and methodsA cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…According to our research, 44.4% of participants used the triple blend without a prescription. This result is similar to another survey when only 26% of the participants took it as recommended by the doctor [ 25 ]. There has been much discussion in most publications about the use of topical steroids without a prescription.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to our research, 44.4% of participants used the triple blend without a prescription. This result is similar to another survey when only 26% of the participants took it as recommended by the doctor [ 25 ]. There has been much discussion in most publications about the use of topical steroids without a prescription.…”
Section: Discussionsupporting
confidence: 89%
“…According to our research, 44.4% of participants used the triple blend without a prescription. This result is similar to another survey when only 26% of the participants took it as recommended by the doctor [25].…”
Section: Discussionsupporting
confidence: 88%
“…11 The topical triple combination known as Kligman's formula has gained popularity among the general population for various purposes. 21,22 The original formula included a mild steroid, dexamethasone 0.1%, in combination with 0.1% tretinoin and 5% hydroquinone in a cream base. This formula has been modified over the years to suit 98 different skin types.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Saudi Arabia involving a total of 292 participants with a mean age of 26.9 years reported that skin redness was the most commonly mentioned side effect of Kligman's formula (61.6%), followed by a burning sensation (50.7%). 21 A study in 20 melasma patients in India using modified Kligman's regimen for 8 weeks showed the most common adverse effects were acneiform eruption, erythema, and burning. 22 Uncontrolled and long-term use of hydroquinone can cause exogenous ochronosis.…”
Section: Discussionmentioning
confidence: 99%